Laparoscopic repair of Amyand's hernia complicated with acute appendicitis. Report of a case. Issue 6 (14th June 2019) - Syllaios, Athanasios; Davakis, Spyridon; Kyros, Eleandros; Lorenzi, Bruno; Charalabopoulos, Alexandros
Abstract: The presence of vermiform appendix in an inguinal hernia sac is known as Amyand's hernia. Amyand's hernia complicated with acute appendicitis is an extremely rare entity with challenging diagnosis and large debate about the optimal treatment option. We report a case of a 58-year-old man presenting to the Emergency Department with an incarcerated right inguinal hernia. At laparoscopy, an inflamed appendix was identified within the inguinal canal, representing an indirect Amyand's hernia. A laparoscopic appendicectomy was performed followed by a trans-abdominal pre-peritoneal mesh repair of the aforementioned hernia. We report this rare clinical entity raising physicians' awareness to include acute appendicitis within an Amyand's hernia in the differential diagnosis of incarcerated inguinal hernias, along with a successful minimally invasive surgical approach.